2016
DOI: 10.1016/j.nut.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D decreases adipocyte lipid storage and increases NAD-SIRT1 pathway in 3T3-L1 adipocytes

Abstract: The observed potent inhibitory effect of 1,25(OH)2D on adipocyte fat storage in mature 3T3-L1 cells suggests that vitamin D might improve adipocyte metabolic function and protect against obesity. Increased NAD concentrations and SIRT1 ​activity may play a role in the mechanism of 1,25(OH)2D action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 50 publications
4
71
1
Order By: Relevance
“…For example, Chang et al [31] recently demonstrated that 1,25(OH) 2 D significantly reduced neutral lipid accumulation in 3T3-L1 adipocytes. Given the role of PC in regulation of lipid accumulation in the same cell line [17], it is possible that 1,25(OH) 2 D exerts its effect on adipocyte lipid accumulation through downregulation of PC, similar to what we have characterized in the present study in malignant breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chang et al [31] recently demonstrated that 1,25(OH) 2 D significantly reduced neutral lipid accumulation in 3T3-L1 adipocytes. Given the role of PC in regulation of lipid accumulation in the same cell line [17], it is possible that 1,25(OH) 2 D exerts its effect on adipocyte lipid accumulation through downregulation of PC, similar to what we have characterized in the present study in malignant breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 protects diet-induced obesity and inflammation and obesity-associated metabolic dysfunction [36,37,38,39]. In addition, vitamin D decreases adipocyte fat accumulation and increases SIRT1 activation in adipocytes [40]. Thus, AMPK and SIRT1 activation have been proposed as key regulators to prevent obesity and obesity-related metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings highlight the role of vitamin D and its active form 1,25(OH)2D in influencing the gene expression of key molecules involved in adipogenesis [12], fat oxidation and lipolysis by the activation of the nicotinamide adenine dinucleotide (NAD)-dependent sirtuin1 pathway [13]. Vitamin D3 has a range of physiological functions in the body, the most important being the maintenance of the calcium and phosphorus balance [14] in osteoblasts, where it usually inhibits cellular proliferation and induces differentiation [15].…”
Section: Introductionmentioning
confidence: 99%